Association between Chinese visceral adiposity index and arterial stiffness among hospital workers in a Chinese tertiary hospital - Guoyu Wang; Peng Gao; Qingqing Zhang; Hong Xu; Jing Zheng; Suyun Jiang; Si Sun; Jingyuan Cao; Li Zhu (Diabetology & Metabolic Syndrome)
Abstract Background Chinese visceral adiposity index (CVAI) has emerged as a reliable marker of visceral adiposity dysfunction. However, its relationship with arterial stiffness has yet to be comprehensively evaluated. This study investigated the association between CVAI and arterial stiffness in a cohort of hospital workers from a tertiary hospital. Methods A cohort of hospital workers aged more than 35 years old, anticipating in physical examinations from September to October 2024, were enrolled in this study. Arterial stiffness was measured by brachial-ankle pulse wave velocity (baPWV). Visceral fat area (VFA) and subcutaneous fat area (SFA) were measured using the umbilical cord level double bioelectrical impedance analyzer. Correlation analysis, univariate and multivariate regression analysis, as well as receiver operating characteristic (ROC) curve analysis were used. Results Our results demonstrated a positive non-linear correlation between CVAI and VFA (p for non-linear: <0.001). CVAI was significantly associated with increased arterial stiffness (odds ratio (OR): 1.033, 95% confidence interval (CI): 1.020–1.046, p <0.001), after adjusting for other confounders. The restricted cubic spline (RCS) analysis indicated a non-linear correlation between the CVAI and arterial stiffness (p for overall: <0.001, p for non-linear: 0.045). The cut-off value of the CVAI for arterial stiffness was 66.11 (sensitivity, 0.711; specificity, 0.620). Conclusions CVAI is an independent predictor of arterial stiffness, suggesting its potential as a clinical tool for identifying individuals at risk of arterial stiffness. Clinical trial number Not applicable.